Dynamics of Temporal and Spatial Transmission of Vaccine-derived Poliovirus (VDPV) in the Democratic Republic of Congo from 2018 to 2023 - Iyala, Jean Blaise Yobo; Degbey, Comlan Cyriaque; Nadakou, N’Kpingou; Tapha, Ounoussa; Soclo, Eveline; Gimiko, Moise; Mawa, Fabrice; Ambanga, Chaltin; Yogolelo, Riziki; Ekanga, Désiré; Onema, Jean Claude (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Background: Vaccine-derived polioviruses (VDPVs) are rare forms of poliovirus that have evolved genetically from the attenuated virus present in oral polio vaccine (OPV). This process occurs during widespread human-to-human transmission in populations with low immunity, or after prolonged replication in the intestines of immunodeficient individuals following vaccination. The Democratic Republic of Congo (DRC) has been facing outbreaks of VDPV since 2017. These wild poliovirus variants are responsible for poliomyelitis, which is in the process of eradication. The following lines show the evolution of VDPV cases across the country in order to understand their chronological dynamics and seasonal influence. Aim: The study aims to analyze the temporal and spatial dynamics of vaccine-derived poliovirus (VDPV) transmission in the Democratic Republic of Congo from 2018 to 2023. Methods: A cross-sectional study was conducted on VDPV and reported in the DRC from 2018 to 2023. Maps of the spatial dynamics of VDPV cases were produced from attack rates with QGIS® (3.22.8). As for temporal dynamics, time series were decomposed and presented in the form of graphs showing the chronological evolution of VDPV cases and their seasonal trend, using R.4.0 software package. Results: A total of 1196 Cases of VDPV types 1, 2 and 3 were recorded in the biological confirmation databases of the INRB and the Expanded Program of Immunization during the study period across 25 provinces. The eastern part of the country reports the most cases. The general trend is upwards, with a peak in 2022 of 527 cases, whereas in 2021 there was a notable drop of 31 cases. The study of the spatiotemporal dynamics of VDPV cases in the DRC (2018 - 2023) highlights a convincing fact, which is spatial heterogeneity. This would be linked to climatic and environmental factors. Analysis of the temporal breakdown suggests a seasonal pattern, with peaks between the months of September and December, considered to be rainy periods in some provinces. Moreover, in endemic countries and areas, PVS has a seasonal pattern that varies according to geographical region. In tropical or semi-tropical regions, PV circulation tends to be cyclical and is often associated with the rainy season. Conclusion: This study of the temporal and spatial dynamics of VDPV has shown the extent of variant poliovirus epidemics and their heterogeneous distribution in the DRC. During the 6 years of the study (2018 - 2023), almost all the Health Zones were hit by VDPV epidemics. The eastern part was the most impacted. The seasonal component is well marked suggesting a rise in detection in the rainy season and during pivotal periods of climate change. This analysis highlights the contribution of the seasonal component to poliovirus circulation; the variation in relative humidity according to season and health zones can partly explain fluctuations in the number of VDPV cases. This result opens the way to taking into account the seasonal component of PV transmission.